The study of anti-ischemic and antidepressant effects of Asparagus cochinchinensis extract - A. .. Zhalsrai; L. T. Sanzhieva (Acta Biomedica Scientifica, 2017)
Extracts of Asparagus cochinchinensis (AC) have antitumor, antiinflammatory, and immunostimulatory effects. The neurobiological mechanisms underlying the effects of AC have not been sufficiently explored. Thus, we performed in vivo experiments to characterize potential therapeutic effects including anti-ischemic and antidepressant activities. In addition, the concentrations of TNF-a and 1L-6 cytokines in blood plasma were measured. In the tail suspension test immobility time was significantly reduced after acute and chronic administration of AC in the dose of 100 and 200 mg/kg which suggests antidepressant activity without effect on body core temperature. After subchronic treatment, the immobility time was significantly different (p < 0.0001). Compared with saline-injected controls, immobility time was reduced in animals treated with 100 mg/kg (p = 0.002) and 200 mg/kg (p < 0.001) respectively. Chronic treatment with AC extract did not change body temperature (p = 0.06). In a pilot study, we measured the effect of subchronically-administered AC extract on infarct size after middle cerebral artery occlusion (MCAO). 1nfarct size in the selected slices is lower in the hippocampus (control -125.9 ± 8.7 μm3; AC - 55.9 ± 22.6 μm3) and striatum (control - 53.8 ± 13.7 μm3; AC -19.7 ± 14.5 μm3) in the animals pretreated with AC. Both cytokines were measured in plasma samples collected from control animals and the experimental groups significantly differed in 1L-6 and TNF-a plasma concentrations. Statistical analysis revealed a significant effect of surgery (control and MCAO; p = 0.006). As regards TNF-α and 1L-6 plasma concentration, there were no differences between the groups (surgery MCAO and treatment AC). This is the first evidence that extract from Asparagus cochinchinensis exerted protective effects in the in vivo MCAO model. However, extract did not effect on the increased levels of cytokine including TNF-α and IL-6.